Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Rentabilitas Ekonomi Pada PT. Argha Karya Prima Industry Tbk - Bambang Kurniawan; Achyat Budianto; Khoiriyatun Ni’mah (Jurnal Publikasi Manajemen Informatika, 2023)
The purpose of this study was to determine and analyze the level of cash turnover, accounts receivable turnover, and economic profitability at PT. Argha Karya Prima Industry Tbk. This study uses a quantitative approach. The type of data used is secondary data. The analysis techniques used are hypothesis testing, classical assumption testing, and multiple linear regression. Based on the results of data analysis, it can be seen that: 1) Partially, cash turnover has no significant effect on economic profitability, with the results of data analysis showing that the value of tcount < table (-0.139 < 2.04227). 2) Partially, accounts receivable turnover has no significant effect on economic profitability, with the results of data analysis showing that tcount < ttable (1.974 < 2.04227). 3) simultaneously there is an influence between cash turnover and accounts receivable turnover on economic profitability, with the results of data analysis showing Fcount > Ftable (3.544 > 3.29).